A global comprehensive review on cultured seafood - Antonio Borriello; Andrea Pierucci (npj Science of Food)
Abstract A comprehensive review of the current state of research on cultured seafood, which identified 40 articles, focuses on six aspects: technology, public health, consumer acceptance, economic viability, environmental impact, and legislation. Findings suggest that this industry is less mature than the cultured meat counterpart, although there is growing interest by private and public stakeholders. More research is needed to explore the complex interplay of these six domains.